Hubungan Terpaan Iklan di Televisi dan Kapabilitas Brand Ambassador Dengan Minat Beli pada Produk Mie Sedaap - Sandra, Syafira; Setyabudi, Djoko (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2020)
The writing of this research was motivated to prove and test about relation of television’s advertising exposure and relation of capability brand ambassador with purchase intentions of Mie Sedaap’s product. . Theories in this research is Strong Advertising Theory and Source of Attractivness Theory. The sampling technique is nonprobability sampling with 100 people for the respondents. The criteria of the sample is men and women aged 16 – 30 who lived in Semarang, Had watched Mie Sedaap’s television advertising, and never buy Mie Sedaap product before (Korean Spicy Chicken Varian). This research used Kendall’s Tau B analysis. The results shows that the significant value of each variable which is advertising exposure and capability of brand ambassador were 0,997 and 0,168 which means had no signigcance related.